Exploring the belief systems of domestic abuse victims: an exploratory study. Issue 1 (13th March 2017) - Spruin, Elizabeth; Baker, Ria; Papadaki, Ioanna; Franz, Anke; Alleyne, Emma
Abstract : Purpose: Support service provisions for domestic abuse victims have typically focussed on the immediate risk and etiological factors associated with abuse. Consequently, there is limited research exploring more persistent and pervasive factors involved in this cycle of abuse, such as subjective experiences and beliefs held by victims of domestic abuse. The purpose of this paper is to preliminary explore individual experience of domestic abuse including the belief systems of participants. Increasing our understanding of key factors and beliefs in the experience of domestic abuse could enable support services to create more long-term sustainable support for victims. Design/methodology/approach: In total, 12 women with a history of domestic abuse participated in an exploratory interview about their general beliefs and thoughts surrounding their domestic abuse experience. Interviews were analysed using thematic analysis. Findings: The thematic analysis identified four belief themes: personal responsibility, antisocial attitudes, environmental factors and negative attitudes towards police. Practical implications: The paper highlights the value of understanding subjective, personalized experiences and beliefs of domestic abuse victims; identifies the importance of belief systems as potential treatment targets for domestic abuse victims; and acknowledges an avenue for more effective support provision for victims of domestic abuse. Originality/value: This preliminary study offers new insights into the role of belief systems amongst a sample of domestically abused women. Understanding the significance of personalized, subjective experiences of domestic abuse victims is a step towards designing and implementing effective interventions. The findings further emphasize the need for more empirical research and theory development within the area of beliefs and domestic abuse victims.